FREQUENCY OF ENDOMETRIAL PATHOLOGY AMONG PERIMENOPAUSAL WOMEN PRESENTING WITH ABNORMAL UTERINE BLEEDING (AUB) (The Research of Medical Science Review, 2025)
Objective: to determine the frequency of endometrial pathology in perimenopausal women presenting with abnormal uterine bleeding (AUB).Study Design: Descriptive cross-sectional studyStudy Setting: Obstetrics and Gynecology Department, JPMC, Karachi.Study Duration: Six months (from June to Nov, 2024)Methodology: This cross-sectional study was conducted at the Department of Obstetrics and Gynecology, Jinnah Postgraduate Medical Centre (JPMC), Karachi. A total of 100 perimenopausal women aged 36-50 years presenting with AUB were included. Endometrial biopsies were performed, and histopathological patterns were analyzed. Data were assessed using SPSS version 21.0.Results: The mean age of participants was 46.6 years, with 72.5% aged between 45-50 years. The most common histopathological finding was proliferative endometrium (36.97%), followed by simple hyperplasia without atypia (14.21%). One case of endometrial carcinoma (1.07%) was identified. Menorrhagia was the most prevalent symptom (40.8%), followed by metrorrhagia (15.9%) and menometrorrhagia (14.0%).Conclusion: AUB is a common gynecological issue in perimenopausal women, with a range of histopathological findings. Routine endometrial assessment should be considered to identify precancerous conditions and enable timely treatment. Further large-scale studies are recommended to refine management strategies.